Unsovereign democracy: why imagination matters in modern politics (and makes religion still relevant) - Paolo Costa (Cauriensia)
The essay articulates the insight that the current crisis of liberal democracies is also a problem of cramped political imagination, which can benefit from the resources of religious imagination, particularly of Christian theological imaginary. If there is a truth emerging from the long history of democratic régimes is that a healthy democracy cannot survive for long without citizen empowerment. Put otherwise, precisely because democracy is a demanding form of self-government, democratic citizens must periodically be fortified in their belief that they have an influence on the direction of their lives. Famously, mass mobilization and protest are among the most effective ways in which this sense of citizen-empowerment is engrained in people’s hearts and minds. This has led some thinkers to stress the role of contestatory politics in that “mise en forme de la société” (C. Lefort), which is ultimately what democracy is all about. Protest, however, needs political institutional channels and outlets in order not to lose its thrust. And it needs as well a coherent social imaginary capable of nourishing the subtle practices of self-government. What happens, then, when its advocates find their main source of motivation and commitment in the rejection of politics or in the problematic allure of a sovereign self? What consequences has this distinctive double bind? And what does it tell us about the future of democracy? Precisely because figuring out an effective form of democratic self-government in modern hyperdiverse societies is hard and embarking in its actualization is a risky, almost utopian enterprise, it makes sense to ask whether there may be an overlap between democratic political imagination and religious imagination in this field. More specifically, the underlying question is whether Christian theological imaginary can bolster people’s trust in human ethical growth and deep transformative potential beyond the model of contestatory democracy as an empowering egalitarian form of self-rule.